Antibody responses to SARS-CoV-2 in patients with COVID-19 - Long, Quan-Xin; Liu, Bai-Zhong; Deng, Hai-Jun; Wu, Gui-Cheng; Deng, Kun; Chen, Yao-Kai; Liao, Pu; Qiu, Jing-Fu; Lin, Yong; Cai, Xue-Fei; Wang, De-Qiang; Hu, Yuan; et al. (Nature medicine, 2020)
We report acute antibody responses to SARS-CoV-2 in 285 patients with COVID-19. Within 19 days after symptom onset, 100% of patients tested positive for antiviral immunoglobulin-G (IgG). Seroconversion for IgG and IgM occurred simultaneously or sequentially. Both IgG and IgM titers plateaued within 6 days after seroconversion. Serological testing may be helpful for the diagnosis of suspected patients with negative RT–PCR results and for the identification of asymptomatic infections. A cross-sectional study of hospitalized patients with COVID-19 and a longitudinal follow-up study of patients with COVID-19 suggest that SARS-CoV2-specific IgG or IgM seroconversion occurs within 20 days post symptom onset.